The Russian-Ukrainian Conflict and its Implications for EU Energy Security - Andreea - Emanuela DRĂGOI; Paul CALANTER; Cornelia NEAGU (Communications of International Proceedings, 2023)
The Russian-Ukrainian conflict is undoubtedly one of the most destabilizing geopolitical event since the end of the Second World War, while its consequences extend both regionally and internationally. For the EU and Russia relations, the most severe implications of this regional conflict are related to the bilateral trade, given that the multiple waves of sanctions imposed on Russia by the European authorities have affected the backbone of this cooperation – the energy trade. Considering this international context, our research aims to identify the impact of the sanctions on bilateral trade, but also to present the implications of the decline of the cooperation between the two states on EU energy security, given that the Russian Federation was, prior the sanctions, the main supplier of natural gas and crude oil to the EU. The quantitative analysis undertaken in this article is based on DG Trade statistics (for EU-Russia trade), but also on a qualitative analysis of the most recently published studies on the impact of sanctions on EU energy security. The objective of our analysis is to highlight the possible solutions found by the EU authorities in the medium and long term for replacing energy imports from the Russian Federation affected by the current trade bans. The limitations of our research are related to the fact that, in addition to the existing sanctions, new ones can be imposed at any time, given that the current Russian-Ukrainian conflict continues and there are no signs that the Russian Federation intends to stop its unprovoked military aggression on Ukraine.
Keywords: Russian-Ukrainian conflict; sanctions; EU – Russia energy trade; EU energy security